A magnetically controlled negative temperature-sensitive hydrogel and its preparation method and application

By combining amphiphilic pentambilical copolymer with magnetic nanoparticles, a magnetron-driven negative temperature-sensitive hydrogel was prepared, which solved the limitations of existing hydrogels in the fields of multiple responsiveness and application, and achieved remote control and wide application of hydrogels.

CN114957716BActive Publication Date: 2025-04-18SOUTHEAST UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210257597.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-16
Publication Date
2025-04-18
Estimated Expiration
2042-03-16

AI Technical Summary

Technical Problem

Existing smart hydrogels have shown limitations in the fields of multiple responsiveness and application, and are difficult to be widely used in more different fields.

Method used

A magnetically driven negative temperature-sensitive hydrogel is prepared by combining amphiphilic pentablock copolymer with magnetic nanoparticles. The directional movement is driven by a magnetic field, which improves its thermal stability, magnetic responsiveness, temperature sensitivity and mechanical stability.

Benefits of technology

Remote control and wide application of hydrogels are realized. The initial thermal decomposition temperature is higher than 300℃ and the maximum magnetic saturation strength is 6.67emu/g. It is suitable for magnetron valves, magnetron circuit switches and damping devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114957716B_ABST
    Figure CN114957716B_ABST
Patent Text Reader

Abstract

The present invention discloses a magnetically controllable negative temperature-sensitive hydrogel, a preparation method and an application thereof. First, a five-block copolymer with amphiphilicity and negative temperature sensitivity is designed and synthesized, and then the hydrophobic magnetic nanoparticles are wrapped inside the block copolymer through the hydrophobic self-assembly effect to prepare the magnetically controllable negative temperature-sensitive hydrogel. The magnetic negative temperature-sensitive hydrogel prepared by the method has good thermal stability, excellent magnetic responsiveness, temperature sensitivity, electrical conductivity and mechanical stability, and can be used for magnetically controlled valves, magnetically controlled circuit switches and damping devices. The preparation method of the present invention is efficient and universal, the raw materials are cheap and easily available, and it has a strong practical application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hydrogel and a preparation method and application thereof, and in particular to a magnetically controllably driven negative temperature-sensitive hydrogel and a preparation method and application thereof. Background Art

[0002] Hydrogel is a hydrophilic polymer with a three-dimensional network structure formed by physical or chemical crosslinking. It can swell but not dissolve in water. It can be divided into traditional and smart hydrogels. Smart hydrogels can respond to external stimuli such as light, temperature, pH, magnetic field, etc., and have been widely studied in many fields such as biomedical materials, biomass sensors, and sewage treatment.

[0003] However, more and more attention is currently focused on the preparation of multi-responsive hydrogels, but their applications are relatively limited and mostly concentrated in the biomedical field. Therefore, it is particularly important to explore the application of smart hydrogels in more different fields. Summary of the invention

[0004] Purpose of the invention: The present invention aims to provide a magnetically controllable negative temperature-sensitive hydrogel having good thermal stability, excellent magnetic responsiveness, temperature sensitivity, conductivity and greater mechanical stability; another purpose of the present invention is to provide a preparation method of the magnetically controllable negative temperature-sensitive hydrogel; another purpose of the present invention is to provide the application of the magnetically controllable negative temperature-sensitive hydrogel in magnetically controlled valves, magnetically controlled circuit switches and damping devices.

[0005] Technical solution: The method for preparing the magnetically controllably driven negative temperature-sensitive hydrogel of the present invention comprises the following steps:

[0006] (1) Adding trimethylene carbonate, poloxamer F127, and stannous isooctanoate into a microwave reactor, reacting in a bulk polymerization manner, cooling to room temperature, dissolving in an organic solvent, and then reprecipitating and freeze-drying to obtain an amphiphilic pentablock copolymer; the amphiphilic pentablock copolymer has a chemical formula of:

[0007]

[0008] wherein m is any value between 0 and 11, and m is not 0; (2) dissolving ferrous sulfate heptahydrate and ferric nitrate nonahydrate in deionized water, and adding ammonia water and oleic acid in sequence under stirring, and obtaining magnetic nanoparticles by reprecipitation and freeze-drying the reaction mixture after the reaction;

[0009] (3) dissolving the pentablock copolymer and magnetic nanoparticles in an organic solvent respectively, mixing the two solutions under stirring, adding deionized water, and stirring at room temperature overnight to obtain a brown-black powder product;

[0010] (4) The brown-black powder product is dissolved in deionized water at a concentration of 5 wt.% to 20 wt.%, thereby obtaining the magnetically controllable negative temperature-sensitive hydrogel.

[0011] Preferably, in step (1), the molar ratio of trimethylene carbonate to poloxamer F127 is 10:1 to 30:1, the organic solvent is dichloromethane, chloroform, tetrahydrofuran, and the reprecipitation solvent used in the reprecipitation method is ether or methanol.

[0012] Preferably, in step (2), the solvent used for the reprecipitation is anhydrous ethanol.

[0013] Preferably, in step (3), the mass ratio of the pentablock copolymer to the magnetic nanoparticles is 10:1 to 20:1, and the organic solvent is dichloromethane, chloroform or tetrahydrofuran.

[0014] The magnetically controllable negative temperature-sensitive hydrogel can be applied to magnetically controlled valves, magnetically controlled circuit switches and damping devices.

[0015] Beneficial effects of the present invention: Compared with the prior art, the present invention has the following significant advantages: (1) The magnetic negative temperature-sensitive hydrogel of the present invention has good thermal stability, excellent magnetic responsiveness, temperature sensitivity, electrical conductivity and mechanical stability. The addition of magnetic nanoparticles greatly solves the problem of remote control of traditional temperature-sensitive hydrogels. The hydrogel can be driven to move in a directional manner by a magnetic field, making the application range of the hydrogel wider. Its initial thermal decomposition (weight loss 5%) temperature is higher than 300°C, and its maximum magnetic saturation intensity is 6.67emu / g; (2) The preparation method of the magnetic negative temperature-sensitive hydrogel of the present invention is efficient and universal, and the raw materials are cheap and easily available, and it has a very high practical application prospect; (3) The magnetic negative temperature-sensitive hydrogel of the present invention can be well applied to magnetically controlled valves, magnetically controlled circuit switches and damping devices due to its excellent comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 1 is a series of characterization diagrams of the magnetic negative temperature-sensitive hydrogel of Example 1, wherein (a) is the infrared spectrum of the magnetic negative temperature-sensitive hydrogel, (b) is the X-ray diffraction diagram, (c) is the hysteresis regression line spectrum, and (d) is the thermogravimetric analysis spectrum;

[0017] Figure 2 This is a rheological test diagram of storage modulus / loss modulus / complex viscosity-temperature of the magnetic negative temperature-sensitive hydrogel in Example 1;

[0018] Figure 3 A digital display diagram and a schematic diagram of a magnetic control circuit switch realized by using a magnetic negative temperature-sensitive hydrogel as a magnetic control valve in Example 1;

[0019] Figure 4 The application diagram (b) and mechanical property test diagram (a) of the magnetic negative temperature-sensitive hydrogel used as a damping device in Example 1;

[0020] Figure 5 Schematic diagram of the structure of magnetic negative temperature-sensitive hydrogel. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0022] The magnetically controllably driven negative temperature-sensitive hydrogel of the present invention has a chemical structural formula as shown in the above formula I, wherein the value of m is any value between 0 and 11.

[0023] Figure 5 Schematic diagram of the structure of magnetic negative temperature-sensitive hydrogel.

[0024] Example 1

[0025] The preparation method of the magnetically controllably driven negative temperature-sensitive hydrogel comprises the following steps:

[0026] (1) Add 0.38g of trimethylene carbonate and 5g of poloxamer F127 (molar ratio of 10:1) to a 50mL microwave reaction bottle, then add 0.11mg of catalyst stannous isooctanoate, and fill the microwave reaction bottle with nitrogen so that the reaction is carried out under nitrogen protection. Place the microwave reaction bottle in a microwave reactor, and react for 5h after the temperature rises to 80°C. After the reaction is completed, cool to room temperature, dissolve the crude product in an appropriate amount of dichloromethane / chloroform / tetrahydrofuran and ultrasonicate until completely dissolved, then use a large amount of ether / methanol for reprecipitation, filter the crude product and collect it, repeat the reprecipitation step 3 times, and freeze-dry (vacuum dry) the product to remove the residual solvent to obtain an amphiphilic pentablock copolymer with negative temperature sensitivity.

[0027] (2) Weigh 1.5g of ferrous sulfate heptahydrate into a 250mL three-necked flask using an electronic balance, add a magnetic stirrer and connect a condenser, then introduce N2 protection, then weigh 4.04g of ferrous nitrate nonahydrate into a 250mL beaker, add 100mL of deionized water to dissolve, and slowly add it to the three-necked flask under magnetic stirring. Heat to 45°C, add ammonia water (8mL) dropwise, react for 30min, add 3mL of oleic acid, heat to 90°C, and react for 1h. After the reaction is completed, cool to room temperature and let stand for 30min. Pour the mixed solution in the three-necked flask into a 1000mL beaker, add an equal volume of anhydrous ethanol to precipitate the magnetic nanoparticles, and separate the crude product of magnetic nanoparticles using a magnet. Wash the crude product three times with deionized water: anhydrous ethanol = 1:1 (volume ratio), and then freeze-dry to obtain hydrophobic magnetic nanoparticles.

[0028] (3) Dissolve 0.1 g of the pentablock copolymer and 0.01 g of magnetic nanoparticles in 1.5 mL and 0.5 mL of dichloromethane, respectively, and perform ultrasonic treatment for 5 min to uniformly disperse them. Stir the copolymer solution with a magnetic bar and slowly add the solution of magnetic nanoparticles to mix them evenly. Continue to slowly drop 2 mL of deionized water under magnetic stirring and stir overnight to allow the dichloromethane to evaporate slowly to obtain a black viscous liquid, which is then freeze-dried to obtain a brown-black solid powder.

[0029] (4) Take 0.1 g of brown-black solid powder and dissolve it in 0.5 mL of deionized water to obtain a magnetic negative temperature-sensitive hydrogel with a mass fraction of 16.7 wt.%.

[0030] Example 2

[0031] The preparation method of the magnetically controllably driven negative temperature-sensitive hydrogel comprises the following steps:

[0032] (1) Add 0.76g of trimethylene carbonate and 5g of poloxamer F127 (molar ratio of 20:1) to a 50mL microwave reaction bottle, then add 0.23mg of catalyst stannous isooctanoate, and fill the microwave reaction bottle with nitrogen so that the reaction is carried out under nitrogen protection. Place the microwave reaction bottle in a microwave reactor, and react for 5h after the temperature rises to 80°C. After the reaction is completed, cool to room temperature, dissolve the crude product in an appropriate amount of dichloromethane / chloroform / tetrahydrofuran and ultrasonicate until completely dissolved, then use a large amount of ether / methanol for reprecipitation, filter the crude product and collect it, repeat the reprecipitation step 3 times, and use freeze drying (vacuum drying) to remove the residual solvent to obtain an amphiphilic pentablock copolymer with negative temperature sensitivity.

[0033] (2) Weigh 1.5g of ferrous sulfate heptahydrate into a 250mL three-necked flask using an electronic balance, add a magnetic stirrer and connect a condenser, then introduce N2 protection, then weigh 4.04g of ferrous nitrate nonahydrate into a 250mL beaker, add 100mL of deionized water to dissolve, and slowly add it to the three-necked flask under magnetic stirring. Heat to 45°C, add ammonia water (8mL) dropwise, react for 30min, add 3mL of oleic acid, heat to 90°C, and react for 1h. After the reaction is completed, cool to room temperature and let stand for 30min. Pour the mixed solution in the three-necked flask into a 1000mL beaker, add an equal volume of anhydrous ethanol to precipitate the magnetic nanoparticles, and separate the crude product of magnetic nanoparticles using a magnet. Wash the crude product three times with deionized water: anhydrous ethanol = 1:1 (volume ratio), and then freeze-dry to obtain hydrophobic magnetic nanoparticles.

[0034] (3) Dissolve 0.1 g of the pentablock copolymer and 0.01 g of magnetic nanoparticles in 1.5 mL and 0.5 mL of dichloromethane, respectively, and perform ultrasonic treatment for 5 min to uniformly disperse them. Stir the copolymer solution with a magnetic bar and slowly add the solution of magnetic nanoparticles to mix them evenly. Continue to slowly drop 2 mL of deionized water under magnetic stirring and stir overnight to allow the dichloromethane to evaporate slowly to obtain a black viscous liquid, which is then freeze-dried to obtain a brown-black solid powder.

[0035] (4) Take 0.1 g of brown-black solid powder and dissolve it in 0.5 mL of deionized water to obtain a magnetic negative temperature-sensitive hydrogel with a mass fraction of 16.7 wt.%.

[0036] Example 3

[0037] (1) Add 1.13 g of trimethylene carbonate and 5 g of poloxamer F127 (molar ratio of 30:1) to a 50 mL microwave reaction bottle, then add 0.34 mg of catalyst stannous isooctanoate, and fill the microwave reaction bottle with nitrogen so that the reaction is carried out under nitrogen protection. Place the microwave reaction bottle in a microwave reactor, and react for 5 h after the temperature rises to 80 ° C. After the reaction is completed, wait until the temperature drops to room temperature, dissolve the crude product in an appropriate amount of dichloromethane / chloroform / tetrahydrofuran, and ultrasonicate until completely dissolved, then use a large amount of ether / methanol for reprecipitation, filter the crude product, and collect it. Repeat the reprecipitation step 3 times. The product is freeze-dried (vacuum dried) to remove the residual solvent to obtain an amphiphilic pentablock copolymer with negative temperature sensitivity.

[0038] (2) Weigh 1.5g of ferrous sulfate heptahydrate into a 250mL three-necked flask using an electronic balance, add a magnetic stirrer and connect a condenser, then introduce N2 protection, then weigh 4.04g of ferrous nitrate nonahydrate into a 250mL beaker, add 100mL of deionized water to dissolve, and slowly add it to the three-necked flask under magnetic stirring. Heat to 45°C, add ammonia water (8mL) dropwise, react for 30min, add 3mL of oleic acid, heat to 90°C, and react for 1h. After the reaction is completed, cool to room temperature and let stand for 30min. Pour the mixed solution in the three-necked flask into a 1000mL beaker, add an equal volume of anhydrous ethanol to precipitate the magnetic nanoparticles, and separate the crude product of magnetic nanoparticles using a magnet. Wash the crude product three times with deionized water: anhydrous ethanol = 1:1 (volume ratio), and then freeze-dry to obtain hydrophobic magnetic nanoparticles.

[0039] (3) Dissolve 0.1 g of the pentablock copolymer and 0.01 g of magnetic nanoparticles in 1.5 mL and 0.5 mL of dichloromethane, respectively, and perform ultrasonic treatment for 5 min to uniformly disperse them. Stir the copolymer solution with a magnetic bar and slowly add the solution of magnetic nanoparticles to mix them evenly. Continue to slowly drop 2 mL of deionized water under magnetic stirring and stir overnight to allow the dichloromethane to evaporate slowly to obtain a black viscous liquid, which is then freeze-dried to obtain a brown-black solid powder.

[0040] (4) Take 0.1 g of brown-black solid powder and dissolve it in 0.5 mL of deionized water to obtain a magnetic negative temperature-sensitive hydrogel with a mass fraction of 16.7 wt.%.

[0041] Figure 1 A series of characterization images of the magnetic negative temperature-sensitive hydrogel in Example 1. Figure 1 (a) is the infrared spectrum of the magnetic negative temperature-sensitive hydrogel at 3500 cm -1 The absorption peak at 2870cm is formed by water peak or hydroxyl in the substance, which is the characteristic peak of hydroxyl; -1 、1100cm -1 The absorption peaks at 1745cm-1 are the absorption peaks of methyl and methylene in the poloxamer F127 block and the stretching vibration absorption peak of the ether bond; -1 There is a strong ester carbonyl absorption peak at 586 cm-1, which indicates that the terminal hydroxyl group of poloxamer F127 reacts with the carboxyl group in the trimethylene carbonate monomer to form an ester and undergoes polymerization. -1 The peak at 1745 cm is the vibration peak of the Fe-O bond in the magnetic nanoparticles. -1 and 586cm -1 An absorption peak appears at , indicating the presence of pentablock copolymers and magnetic nanoparticles. Figure 1(b) is the X-ray diffraction pattern of the magnetic negative temperature-sensitive hydrogel. It can be seen from the figure that the strong peak in the magnetic hydrogel is the characteristic peak of the copolymer, and there is also a diffraction peak of the magnetic nanoparticles, which indicates that the hydrophobic self-assembly process does not destroy the magnetism and crystal form of ferroferric oxide, and the product is in good crystallization condition. Figure 1 (c) is the hysteresis loop of the magnetic thermosensitive hydrogel at 300K. It can be seen from the figure that with the increase of the external magnetic field, the magnetic saturation intensity of the magnetic thermosensitive hydrogel also increases, and there is no remanent magnetism and coercive force, showing superparamagnetism, and the maximum magnetic saturation intensity is 6.67emu / g. Figure 1 (d) is the thermogravimetric analysis diagram of the magnetic negative temperature-sensitive hydrogel. It can be seen from the figure that its initial thermal decomposition (weight loss 5%) temperature is higher than 300°C, which indicates that the hydrogel has good thermal stability and can meet some demanding application requirements.

[0042] Figure 2 This is a rheological test diagram of storage modulus / loss modulus / complex viscosity-temperature of the magnetic negative temperature-sensitive hydrogel in Example 1. Figure 2 It can be seen that at 20°C, the copolymer solution exhibits fluid properties, and the loss modulus (G") is about 0.56Pa, which is higher than the storage modulus (G', ~0.022Pa). At this time, the viscosity (η) is less than 0.1Pa·s. In the range of 28°C to 40°C, the viscosity of the copolymer solution increases sharply, reaching a maximum of 1.2×10^6mPa·s. The change in viscosity indicates that the degree of gelation of the copolymer solution gradually increases. The result is consistent with the measurement results of the inverted bacterial bottle. When it reaches 40°C, the inverted bacterial bottle shows complete gelation. With the increase of temperature, the storage modulus of the magnetic hydrogel increases sharply between 22°C and 30°C, and stabilizes when the temperature rises to about 30°C, reaching 10000Pa, which is 10 times the loss modulus, showing a gel state. Therefore, in order to ensure that the magnetic hydrogel has excellent mechanical properties, we choose 40°C as the temperature for complete gelation of the magnetic hydrogel.

[0043] Figure 3The digital display diagram and magnetically controlled circuit switch schematic diagram of Example 1 using magnetic negative temperature-sensitive hydrogel as a magnetically controlled valve. As shown in Figure (a), we built a "sun"-shaped pipeline, filled it with n-hexane fluid, and injected magnetic hydrogel into it. Under the control of a magnet, it can be separated into multiple magnetic droplets. The distribution of magnetic droplets at different intersections of the pipeline is changed by using a magnet. After the magnetic droplets are distributed at different intersections, they are irradiated with 808nm near-infrared light to gel and act as a valve, thereby realizing the digital display of 0 to 9 of colored fluid in the pipeline. As shown in Figure (b), based on the excellent conductivity of magnetic nanoparticles, it is possible for the magnetic hydrogel to connect the circuit as an intelligent conductor through magnetic field control. The sol-state magnetic hydrogel can connect the circuit by moving the magnet, and even if the magnet is removed, the circuit will remain connected after gelation. First, the magnetic hydrogel is injected into a transparent quartz tank with two electrodes on both sides. The flowing magnetic hydrogel can be attracted to the wall of the quartz tank by the magnet, thereby connecting the two electrodes and lighting up the LED light. However, when the magnet is removed, the circuit is gradually disconnected, causing the LED light to go out. The magnetic hydrogel is then exposed to 808nm near-infrared light for a few seconds. After the magnetic hydrogel is in a gel state, the circuit remains connected even after the magnetic field is removed, and the LED light is still lit. After gradually returning to room temperature, the circuit can also be disconnected.

[0044] Figure 4The application diagram (b) and mechanical properties test diagram (a) of the magnetic negative temperature-sensitive hydrogel used as a damping device in Example 1 are shown in Figure (a). As shown in Figure (a), due to the negative temperature sensitivity of the hydrogel, it maintains a sol state at low temperatures and has a certain fluidity. It can be combined with porous materials at low temperatures and transformed into a gel state after being heated to the gelation temperature. Therefore, we first compared the difference in mechanical properties of the blank sponge and the sponge filled with hydrogel after gelation by dynamic mechanical analysis (DMA) at 40°C. It can be seen that when the compression strain is 40%, the compressive stress of the sponge filled with hydrogel is 16kPa, which is much higher than the compressive stress of the blank sponge (4kPa). At the same time, the blank sponge can achieve 80% reversible deformation, while the sponge filled with hydrogel can only be compressed to 45% of the deformation, and it is irreversible. This irreversible phenomenon may be related to the viscosity of the gel. In short, these mechanical properties enable magnetic hydrogels to be used as filling materials for buffer devices or for micro dampers. As shown in Figure (b), we conducted a drop ball test to evaluate the mechanical dissipation and impact mitigation capabilities of magnetic hydrogels under dynamic loads. A 25cm high ball drop test device was built with an iron stand. A blank sponge with a width of 25mm, a length of 25mm, and a thickness of 5mm and a sponge of the same size filled with hydrogel were placed on the top layer, the middle layer was a glass slide (25mm wide, 75mm long, and 1mm thick), and the bottom layer was a tabletop as a support layer to form a three-layer assembly. A 50g stainless steel ball was then used as the falling body. The appearance of the stainless steel ball in the ball drop test is shown in Figure (b). It can be seen that the glass slide under the blank sponge was broken. In contrast, when the stainless steel ball fell from the same height onto a sponge of the same geometry filled with hydrogel, the glass slide was in good condition. The comparison results show that the gelled hydrogel has a good protective effect on the glass slide under severe dynamic loads and has good shock absorption capacity. Therefore, the magnetic hydrogel can be used as a buffer layer at a specific temperature to achieve a damping effect.

Claims

1. A method for preparing a magnetically controllable negative temperature-sensitive hydrogel, characterized in that: The following steps are involved: (1) Adding trimethylene carbonate, poloxamer F127, and stannous isooctanoate into a microwave reactor, reacting in a bulk polymerization manner, cooling to room temperature, dissolving in an organic solvent, and then reprecipitating and freeze-drying to obtain an amphiphilic pentablock copolymer; the chemical structure of the amphiphilic pentablock copolymer is: , wherein m is any value between 0 and 11, and m is not 0; (2) dissolving ferrous sulfate heptahydrate and ferric nitrate nonahydrate in deionized water, and adding ammonia water and oleic acid in sequence under stirring, and obtaining magnetic nanoparticles by reprecipitation and freeze-drying the reaction mixture after the reaction; (3) dissolving the pentablock copolymer and magnetic nanoparticles in an organic solvent respectively, mixing the two solutions under stirring, adding deionized water, and stirring at room temperature overnight to obtain a brown-black powder product; (4) The brown-black powder product is dissolved in deionized water at a concentration ranging from 5 wt.% to 20 wt.%, thereby obtaining the magnetically controllable negative temperature-sensitive hydrogel.

2. The method for preparing the magnetically controllable negative temperature-sensitive hydrogel according to claim 1, characterized in that: In step (1), the molar ratio of trimethylene carbonate to poloxamer F127 is 10:1 to 30:

1.

3. The method for preparing the magnetically controllably driven negative temperature-sensitive hydrogel according to claim 1, characterized in that: In step (1), the organic solvent is dichloromethane, chloroform or tetrahydrofuran.

4. The method for preparing the magnetically controllably driven negative temperature-sensitive hydrogel according to claim 1, characterized in that: In step (1), the reprecipitation solvent used in the reprecipitation method is ether or methanol.

5. The method for preparing the magnetically controllably driven negative temperature-sensitive hydrogel according to claim 1, characterized in that: In step (2), the solvent used for the reprecipitation is anhydrous ethanol.

6. The method for preparing the magnetically controllably driven negative temperature-sensitive hydrogel according to claim 1, characterized in that: In step (3), the mass ratio of the pentablock copolymer to the magnetic nanoparticles is 10:1 to 20:

1.

7. The method for preparing the magnetically controllably driven negative temperature-sensitive hydrogel according to claim 1, characterized in that: In step (3), the organic solvent is dichloromethane, chloroform or tetrahydrofuran.

8. A magnetically controllably driven negative temperature-sensitive hydrogel prepared by the preparation method according to any one of claims 1 to 7.

9. An application of the magnetically controllable negative temperature-sensitive hydrogel according to claim 8 in magnetically controlled valves, magnetically controlled circuit switches and damping devices.

Citation Information

Patent Citations

  • Temperature sensing parents block polymer / iron oxide magnetic nano-carrier, preparation method and application thereof

    CN101219218A

  • Temperature-sensitive hydrogel based on chemical cross-linking gel granules and preparation method of temperature-sensitive hydrogel

    CN102146200A